A teoria de Duffin-Kemmer-Petiau - Cardoso, T. R. [UNESP]; Pimentel, B. M. [UNESP] (FapUNIFESP (SciELO), 2016)
The theory of Duffin-Kemmer-Petiau is presented from a historical point of view, highlighting the ideas and analogies which led to its formal development, as well as to its algebra and general properties. Furthermore, some misunderstood concepts surrounding the massless limit, m = 0, as well as the equivalence between this formalism and the formalisms of Klein-Gordon-Fock and Proca, for free and minimal coupling cases, are exposed. Insofar the completion of this study with the richness of the possible phenomenological interactions that make the theory of Duffin-Kemmer-Petiau a source of inspiration and culture.
The theory of Duffin-Kemmer-Petiau
Keywords: Duffin-Kemmer-Petiau algebra; Duffin-Kemmer-Petiau theory; First-order equation; Klein-Gordon-Fock equation; Proca equations